Chromatin Accessibility Is Associated with Artemisinin Biosynthesis Regulation in Artemisia annua - Zhou, Limeng (Molecules, 2021)
Glandular trichome (GT) is the dominant site for artemisinin production in Artemisia annua. Several critical genes involved in artemisinin biosynthesis are specifically expressed in GT. However, the molecular mechanism of differential gene expression between GT and other tissue types remains elusive. Chromatin accessibility, defined as the degree to which nuclear molecules are able to interact with chromatin DNA, reflects gene expression capacity to a certain extent. Here, we investigated and compared the landscape of chromatin accessibility in Artemisia annua leaf and GT using the Assay for Transposase-Accessible Chromatin using sequencing (ATAC-seq) technique. We identified 5413 GT high accessible and 4045 GT low accessible regions, and these GT high accessible regions may contribute to GT-specific biological functions. Several GT-specific artemisinin biosynthetic genes, such as DBR2 and CYP71AV1, showed higher accessible regions in GT compared to that in leaf, implying that they might be regulated by chromatin accessibility. In addition, transcription factor binding motifs for MYB, bZIP, C2H2, and AP2 were overrepresented in the highly accessible chromatin regions associated with artemisinin biosynthetic genes in glandular trichomes. Finally, we proposed a working model illustrating the chromatin accessibility dynamics in regulating artemisinin biosynthetic gene expression. This work provided new insights into epigenetic regulation of gene expression in GT.